Choosing a Licensed Wood-Destroying Organism (WDO) Inspector - Faith M. Oi; Paul Mitola; Kathleen C. Ruppert; Michael J. Page; Mark H. Ruff (EDIS, 2016)
A wood-destroying organism inspection is a visual inspection performed by a licensed pest control inspector trained to identify evidence of termites, powderpost beetles, and other organisms that chew on wood and cause damage to property. Home buyers and sellers, real estate professionals, and lending institutions order these inspections before real estate transactions. This revised 4-page fact sheet explains how to select an inspector who is licensed and certified so that you can be confident in the inspection. Written by Faith M. Oi, Paul Mitola, Kathleen Ruppert, Michael Page, and Mark Ruff, and published by the Entomology and Nematology Department, July 2015.